Flexible and transparent graphene complementary logic gates. Issue 3 (13th March 2019) - Dathbun, Ajjiporn; Kim, Seongchan; Lee, Sungjoo; Hwang, Do Kyung; Cho, Jeong Ho
Abstract : Flexible and transparent monolithic graphene transistors and complementary logic gates were fabricated using chemically doped graphene. Abstract : In this study, flexible and transparent monolithic graphene transistors and complementary logic gates were fabricated using chemically doped graphene. The graphene channel was p- and n-doped with bis-(trifluoromethanesulfonyl)amine and poly(ethylene imine), respectively. Ion gel was utilized to gate the graphene transistor, and this facilitated low-voltage operation and yielded a coplanar-gate geometry. The resulting monolithic graphene transistors exhibited p-type or n-type transport depending on the type of dopant. The p-type and n-type graphene transistors were assembled together to fabricate various logic circuits, e.g., NOT, NAND, and NOR gates. Overall, the selective chemical doping of graphene enabled the realization of complementary logic gates, which represents a significant step in the application of graphene to future two-dimensional-based electronic devices.